Metal–organic framework‐derived high‐performance polypyrrole/Ni‐CAT/PI fiber paper‐based electromagnetic shielding composites for high‐frequency electromagnetic wave absorption. Issue 12 (11th November 2022) - Zhang, Ruqiang; Lv, Wenzhi; Zhu, Ruifeng; Zhang, Dan; Wang, Shihua; Long, Zhu
Abstract: Light‐weight, portability and miniaturization are important characteristics for the next generation of high‐performance electromagnetic interference (EMI) shielding equipment. To meet the current demand for high‐performance EMI shielding materials, this paper proposes a simple and reliable method for preparing multilayer paper‐based composites. Paper‐based composites exhibit light weight, flexibility, easy processing and high temperature resistance. A conductive metal–organic skeleton (Ni‐CAT) layer and polypyrrole (PPy) layer were deposited on a polyimide (PI) fiber surface with an in situ synthesis and gas aggregation method to prepare paper‐based electromagnetic shielding composites with good properties. The results showed that the electromagnetic shielding effect (SE) of the paper‐based composites reached 41.0 dB. After the paper‐based composites underwent multiple ultrasonic washing and bending tests, their electrical conductivity retention rate was as high as 90%. Furthermore, the introduction of PPy/Ni‐CAT enhanced the bonding strength of the PI fibers, which caused the tensile strength of the paper‐based composites to reach 22.3 MPa. Due to the good thermal stability of the composites, they can withstand an open flame and protect the equipment during a fire. Thus, these paper‐based EMI shielding composites hold great promise for flexible electromagnetic shielding materials, protection of smart wearable devices and other fields. Abstract : The electromagnetic shielding mechanism diagram of the PPy/Ni‐CAT/PI fiber paper‐based composites and the electromagnetic shielding effectiveness in the X‐band.